SPONTANEOUS RESOLUTION OF SCIATICA IN LUMBAR DISC EXTRUSIONS - Micunovic, Micun Mile; Mircevski, Vladimir; Shibakoska, Ana; Sheshoski, Ognen; Micunovic, Emilija; Stevoski, Aleksandar; Dodevski, Ace (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
Sciatica is a common disturbance that presents itself with an excruciating pain in the leg accompanied with paresthesia or dysesthesia along the leg which can disable patients with their everyday activities. The aim of this study is to present cases of sciatica with spontaneous resolution. We present 9 illustrative cases of patients with sciatica caused by extrusion of lumbar disc who recovered spontaneously within a year of follow-up. The patients were examined and treated in the Specialized Hospital for Orthopedic Surgery and Traumatology â€œSt. Erazmoâ€ in Ohrid, R. Macedonia in the period of 2018 to 2020. Eight of nine patients were suggested to be treated by surgery because of the symptoms of sciatica and the magnetic resonance findings of the lumbar spine, but they refused. The cases present patients with sciatica caused by lumbar disc extrusion which resolved spontaneously without surgery. Patients should be indicated for magnetic resonance imaging for precise indications, not only for acute onset of leg pain caused by sciatica. Conservative treatment should be considered as an option for treatment of sciatica.             Key words: spontaneous resolution, sciatica, extrusion